The Impact of Sexual Harassment on Work Attitudes in Tertiary Educational Institutions in Delta State - Nwokocha, N. Lilian; Ayewumi, Akpobolokemi Andrew; Okolie, Ugo Chuks (Universitas Kuningan, 2025)
This study explores the impact of sexual harassment on key work attitudes job satisfaction, employee commitment, and job engagement in tertiary educational institutions in Delta State, Nigeria. Utilizing both correlation and multiple regression analyses, the study consistently finds that sexual harassment negatively influences these work attitudes. Specifically, increased levels of sexual harassment correlate with decreased job satisfaction, lower employee commitment, and reduced job engagement among employees. These findings highlight the dual role of sexual harassment as both a violation of employee rights and a major barrier to employee productivity and well-being within academic institutions. The research underscores the particular concern regarding the negative effects of harassment on employee commitment and engagement. Employees who experience sexual harassment are more likely to feel disengaged from their work and less emotionally invested in their roles. This disengagement not only impacts individual morale but also threatens overall organizational performance, potentially undermining the academic environment and institutional success. The study advocates for a proactive approach in tertiary institutions to address sexual harassment, emphasizing the importance of creating a safer and more inclusive work environment that prioritizes the well-being of employees. In light of these findings, the study proposes several recommendations for tertiary institutions in Delta State, Nigeria, to mitigate the impact of sexual harassment. These include implementing comprehensive anti-harassment policies, conducting regular training and awareness programs, establishing safe and confidential reporting mechanisms, promoting organizational support for victims, and regularly monitoring and evaluating the effectiveness of harassment prevention measures. By adopting these strategies, academic institutions can enhance employee satisfaction, commitment, and engagement, fostering a more positive and productive academic culture.